Perencanaan dan Pengorganisasian Kepala Madrasah Dalam Peningkatan Mutu Lembaga Pendidikan: (Studi Multi Situs di Madrasah Aliyah Negeri 1 dan Madrasah Aliyah Negeri 3 Kabupaten Tulungagung Provinsi Jawa Timur) - Ali Mashar (Sustainable, 2021)
The effort to release Islamic education institution which is consistent with superior qualification needs practical steps. Islamic education institution such as general school with Islamic identity in management. Data collected method in this case study using direct observation technique, communication technique and also documentation technique. In Data Analysis method, the researcher uses descriptive analysis technique. The researcher does interpretation by deductive, inductive and cooperative thinking reasonable in analysis process to the result of the research. Need strategic planning of MAN 1 Tulungagung and MAN 3 Tulungagung headmaster in developing education institution and the strategic organization of MAN 1 Tulungagung and MAN 3 Tulungagung headmaster in developing education institution.